Mechanics of Composite Materials with MATLAB - Voyiadjis, George Z.; Kattan, Peter I. (Springer Berlin Heidelberg : Imprint: Springer, 2005)
This textbook makes use of the popular computer program MATLAB as the major computer tool to study Mechanics of Composite Materials. It is written specifically for students in Engineering and Materials Science examining step-by-step solutions of composite material mechanics problems using MATLAB. Each of the 12 chapters is well structured and includes a summary of the basic equations, MATLAB functions used in the chapter, solved examples and problems for students to solve. The main emphasis of Mechanics of Composite Materials with MATLAB is on learning the composite material mechanics computations and on understanding the underlying concepts. The solutions to most of the given problems appear in an appendix at the end of the book.